A local digital network to support teaching and learning in Physics (Research, Society and Development, 2021)
Several contemporary proposals for teaching physics contemplate the use of computational technologies. However, not all schools or non-formal teaching environments have the resources and essential connectivity to participate and keep up all the dynamics triggered by the dissemination of information via technologies and favor their use in learning and teaching. In this context, we propose a teaching platform involving hardware and software, created with the purpose of mitigating this problem and enabling the connection of mobile devices to a repository of didactic resources. The method used characterizes this work as applied research, exploratory with a qualitative approach. The central component of the platform is ESP-32 microcontroller used to generate a minimal, reach-out digital network infrastructure restricted to a single teaching environment, such as inside classrooms. As proof of concept of project viability, the platform was tested in a face-to-face class about electrical circuits in a third-year high class of the southern Minas Gerais state public school. The results on the feasibility in the current phase of development of the project are encouraging enough to encourage its continuation, investment in time, and resources to expand and enhance it.